2020
DOI: 10.1111/maps.13598
|View full text |Cite
|
Sign up to set email alerts
|

Mantle–melt partitioning of the highly siderophile elements: New results and application to Mars

Abstract: Trace elements and extant and extinct isotopic attributes in Martian meteorites have been used to argue that Mars accreted quickly, differentiated into core and mantle, and established several mantle reservoirs, possibly within 10 Ma of T0. The partitioning of trace elements in the deep mantle has been relatively unstudied, despite the need for such knowledge in understanding magma ocean crystallization and the origin of depleted and enriched mantle reservoirs. The siderophile element composition of the Martia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…Such signatures would contrast with the lower Ru/Ir ratios observed among Hawaiʻi and Iceland OIB. Although there is a paucity of data indicating how Ru and Ir would behave during subsequent basal magma ocean crystallization, an experimental study of Ru and Os has revealed no significant difference in partitioning among deep-mantle phases (Righter et al, 2020). Since IPGE generally behave similarly during mantle melting, this is a priori evidence that Ru/Ir ratios would not be strongly altered by this process.…”
Section: Alternative Models Generating Negative µ 182 W In Hadean-arc...mentioning
confidence: 98%
“…Such signatures would contrast with the lower Ru/Ir ratios observed among Hawaiʻi and Iceland OIB. Although there is a paucity of data indicating how Ru and Ir would behave during subsequent basal magma ocean crystallization, an experimental study of Ru and Os has revealed no significant difference in partitioning among deep-mantle phases (Righter et al, 2020). Since IPGE generally behave similarly during mantle melting, this is a priori evidence that Ru/Ir ratios would not be strongly altered by this process.…”
Section: Alternative Models Generating Negative µ 182 W In Hadean-arc...mentioning
confidence: 98%
“…In some contexts P likely behaves as a volatile element during planetary accretion. Under some melt conditions, it is an incompatible element, and sometimes it also behaves as a siderophile element [10]. This latter behavior may best explain its depletion in Earth's upper geological reservoirs (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The oxidation state of P in the environment is governed by the kinetics and stoichiometry of electrons from other easily exchanged donor and acceptor elements, most importantly Fe, S and C [18]. Consideration of the oxidation state of the BSE over time suggests that P remaining in the BSE after core formation would have continuously experienced global redox conditions maintaining it in the +5 oxidation state [8,10], though localized reservoirs hosting reduced P are also possible. In modern terrestrial surface environments, P is generally encountered in the +5 state, though there is some evidence for widely distributed, though minor, reduced P [19], and the widespread distribution of genes for the oxidation of reduced phosphorus suggests there is a significant biologically exploitable reservoir of reduced P [20].…”
Section: Introductionmentioning
confidence: 99%